Infection due to Buteo buteo herpesvirus in a common buzzard (Buteo buteo insularum) - Cristian M. Suárez-Santana; Eva Sierra; Lucía Marrero-Ponce; Ana Colom-Rivero; Jose Navarro-Sarmiento; Simone Segura-Göthlin; Ayoze Castro-Alonso; Óscar Quesada-Canales (Frontiers in Veterinary Science, 2023)
This study aimed to document the pathological findings observed in a common buzzard (Buteo buteo insularum) from Gran Canaria (Canary Islands, Atlantic Ocean), naturally infected with Buteo buteo herpesvirus (HV). Local authorities found the common buzzard alive, but it died after 10 days of specialized veterinary care. Postmortem investigation, including complete gross and histologic examination, immunohistochemistry, microbiology, and PCR, was performed. The animal presented necrotizing heterophilic and histiocytic bilateral conjunctivitis, stomatitis, pharyngitis, rhinitis, and sinusitis with secondary bacterial and fungal infections. Frequent eosinophilic intranuclear inclusion bodies were observed in the oral mucosa and esophagus epithelium. HV proteins and DNA were detected in tissues from this animal. The sequences obtained from the PCR product were identical to the reported sequences of Buteo buteo HV.